Programa de capacitación docente sobre educación sexual para fortalecer el papel como orientador en el colegio Pío Jaramillo Alvarado sección matutina periodo lectivo 2012-2013 - Tandazo Ludeña, Lorena (2014)
This research is based on the study of the teacher training program on sexual education to strengthen the role as a mentor in the College Pío Jaramillo Alvarado morning section 2012 school year - 2013 The purpose of the research is to improve teacher preparation in content sex education program on sexual orientation information to teachers that can enhance and update their knowledge and provide their students clear and adequate information to enable them to prevent negative consequences such as unwanted pregnancies , sexually transmitted diseases and abortions to throughout his life, trying to strengthen the role of teachers and counselors at school Pio Jaramillo Alvarado on sexual education .. research corresponded to a descriptive theoretical design methods it was used as the historical and logical, analytical -synthetic , inductive-deductive , empirical, statistical and descriptive ; which were implemented after document review techniques such as surveys , interviews ; their results were derived mainly that teachers have little training on sexual education that allows them to learn teaching strategies to inform students and they acquire new knowledge about the same .